The development of 3d augmented reality learning media to enhance students’ motivation in learning calculus - Rahmanto, Pramudita; Ismaniati, Christina; Hidayah, Nurul (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study aims to develop innovative learning media utilizing 3D Augmented Reality (AR) technology based on mathematical investigation to enhance student motivation in studying calculus. The research follows the Research and Development (R&D) method, adopting the 4D model which includes four stages: Define, Design, Develop, and Disseminate. Data collection involved validity, practicality, and effectiveness test instruments. The results indicate: (1) the validity of the media, evaluated by three expert validators, achieved an average score of 4.5933, categorized as very valid; (2) the practicality, based on student responses after using the media, reached an average of 92.27% across assessed aspects; and (3) the effectiveness test, through a comparison of pretest and posttest scores using a paired t-test and n-gain analysis, showed a learning outcome improvement with a gain score of 48.9429%. The developed media successfully integrates calculus concepts with interactive and immersive visualizations through 3D AR, offering students the opportunity to explore mathematical concepts more intuitively and engagingly. This approach demonstrates promising potential in increasing motivation and improving learning outcomes in calculus education.